A preliminary environmental assessment of power generation systems for a stand-alone mobile house with cradle to gate approach - (:unkn) unknown (Gazi Universitesi, 2011)
Due to the sporadic characteristics of solar and wind power it has been a challenge to generate a highly reliable power with photovoltaic and or wind turbines alone. A fuel cell as a supplementary energy source is an alternative to overcome this challenge. PV/wind/fuel cell hybrid power system may be a feasible solution for stand-alone applications. In this study, which is a preliminary work of a comprehensive Life Cycle Assessment (LCA), comparison of the power generation alternatives in terms of environmental impacts by evaluating their environmental and energy efficiencies and impacts during the productions of the system components was given. Also, impacts during the production of wind turbines, PV panels, fuel cells and diesel generators were inspected. Eco-Indicator 99 impact assessment method was used as the impact assessment method. It was shown that the in human health and ecosystem quality damage categories the PV panels are less environmentally efficient when compared with other power generation technologies with similar capacities.
Keywords: Fuel cell; Life cycle assessment; Photovoltaic; Stand-alone; Wind